New generation of paediatricians in the health care system: are paediatric residents ready to manage children without supervision? A survey using respiratory infections as a model - Alfredo Guarino; Francesca Rossi; Margherita Del Bene; Alfredo Diana; Antonio Corsello; Francesco Cecere; Cristiana Indolfi; Enza Mozzillo; Francesco Nunziata; Filomena Pascarella; Michelina Sibilio; Massimo Ummarino (BMJ Open, 2025)
Objectives To measure the perceived autonomy level in managing lower respiratory tract infections (LRTIs) among paediatric residents and to compare perceived autonomy with the assessments by tutors who directly supervise and evaluate residentsDesign/setting A survey on managing LRTIs was distributed among all Italian paediatric residents and tutors via Google Forms between January 1 and 31, 2024.Participants, residents and tutors were classified according to their training year and clinical setting: primary care paediatrics (PCP), emergency department (ED) and hospital ward (HW).Outcome Perceived autonomy of paediatric residents in managing LRTI in different settings; overall perceived autonomy and interest in employment.Results A total of 391 questionnaires were returned, with 273 completed by residents and 118 by tutors. Among residents, 3% in their first year felt fully capable of managing LRTIs without supervision in both ED and HW settings. This percentage remained below 25% until the third year and increased to 72% in ED and 83% in HW by the fifth year. In PCP settings, autonomy ranged from 15% in the first year to 96% in the final year. No differences were found between residents’ self-evaluations and tutors’ assessments. Confidence in skills showed no regional differences across Italy.Conclusion Most residents did not feel ready to manage winter respiratory infections in children without supervision, especially in the ED compared with the HW; however, self-confidence was higher in the PCP setting. Tutors shared similar perceptions. The location did not affect the response pattern. These findings caution against employing residents to work autonomously, particularly in emergency settings.